Механiзм швидкого аксiально симетричного перемикання полярностi магнiтного вихору - Pylypovskyi, O. V.; Sheka, D. D.; Kravchuk, V. P.; Gaididei, Yu. B.; Mertens, F. G. (Publishing house "Academperiodika", 2018)
The magnetic vortex core in a nanodot can be switched by an alternating transversal magnetic field. We propose a simple collective coordinate model, which describes the comprehensive vortex core dynamics, including the resonant behavior, weakly nonlinear regimes, and reversal dynamics. A chaotic dynamics of the vortex polarity is predicted. All analytical results are confirmed by micromagnetic simulations.